Changing trends in the indications of obstetric hysterectomies in teaching rural hospital - Moray, Arun P.; Moray, Urmila A.; Patil, Vaishali M.; Moray, Grishma A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Obstetric hysterectomy (OH) still remains lifesaving procedure. OH still poses a major obstetrical morbidity in the developing world due to lack of human, infrastructural and monetary resources. Irrespective of attempts like good antenatal care and delivery planning in modern obstetrics to prevent major obstetric complications; unfortunately, OH needs to be performed at times even today. The aim of present study was to determine the changes in the indications of obstetric hysterectomy. Methods: A retrospective review based on hospital data of all the patients’ records subjected to OH from January 1994 to September 2001 (Gr. A) and from January 2006 to December 2015 (Gr. B) was done and analyzed for incidence and changing trends in the indications. Results: The incidence of OH during two periods from January 1994 to September 2001 (Group A) and from January 2006 to December 2015 (Group B) in the Department of Obstetrics and Gynecology at Shri. Bhausaheb Hire Govt. Medical College, Dhule was 3.27/1000 and 0.97/1000 deliveries. Incidence is reduced by more than three folds. In both groups maximum patients were below 30 yrs of age and multipara. The commonest indications for OH in both groups were uterine rupture, uncontrolled Atonic PPH and placental causes. The incidence of uterine rupture as a cause for OH was reduced from 78.16% to 43.24%, while that of Atonic PPH has increased from 16.09% to 28.37% and placental causes has increased from 4.59% to 9.45%. Among the risk factors for OH, the incidence of prolonged or obstructed labour has reduced from 66.66% to 21.62% and that of malpresentations has reduced from 27.58 to 5.4%. Conclusions: There is definite reduction in the incidence of OH, frequency of uterine rupture, obstructed labor and malpresentations in Gr. B due to timely referral, improved infrastructure and transportation facilities.